A tale of two moralities: Politicians, doctors, use of addictive substances and lobbying. (July 2018) - Venkataraman, Ashwin; Nutt, David
Alcohol use during the day is common amongst British MPs and Parliamentary staff even when Parliament is in session. MPs are frequently under the influence of alcohol when deciding on important bills, potentially affecting their judgement. Lobbying from the alcohol and the tobacco industries is rife in Parliament. What hope is there to change alcohol and tobacco policy in a more rational and healthy direction if the companies responsible for their harms are corrupting the political process in this fashion? We propose recommendations in line with the standards required for doctors.